Republic of Moldova : Technical Assistance Report-National Accounts Statistics Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
A national accounts statistics mission provided remote technical assistance in national accounts to the National Bureau of Statistics of Moldova (NBS) during January 17-28, 2022. The NBS has received extensive technical assistance from the IMF in recent years and has made good progress in improving the national accounts compilation. The GDP estimates are compiled according to the System of National Accounts, 2008. Recent national accounts technical assistance missions have assisted the NBS in improving the quarterly estimates of GDP, implementing chain-linked volume measures, and implementing the Statistical Classification of Economic Activities in the European Community (NACE revised2), among other areas. The mission assisted in improving the annual GDP estimates for 2014 to 2020, to take account of revised population data and other additional source data. Estimates of GDP in current prices by production and by expenditure categories were reviewed and improved. Estimates of GDP in volume terms (at prices of the previous year) were compiled by production and expenditure categories. Both sets of GDP estimates were balanced at current prices and in volume terms. The mission recommended that, to improve the consistency and accuracy of the GDP estimates, the NBS develop a system to compile supply and use tables on a regular basis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Moldova, Republic of